Wide‐Gap Perovskite via Synergetic Surface Passivation and Its Application toward Efficient Stacked Tandem Photovoltaics. Issue 8 (6th December 2021) - Huang, Tianyi; Wang, Rui; Nuryyeva, Selbi; Tan, Shaun; Xue, Jingjing; Zhao, Yepin; Wu, Quantan; Weber, Marc H.; Cheng, Pei; Meng, Dong; Yavuz, Ilhan; Houk, K. N.; et al.
Abstract: Superior bandgap tunability enables solution‐processed halide perovskite a promising candidate for multi‐junction photovoltaics (PVs). Particularly, optically coupling wide‐gap perovskite by stacking with commercially available PVs such as silicon and CIGS (also known as 4‐terminal tandem) simplifies the technology transfer process, and further advances the commercialization potential of perovskite technology. However, compared with matured PV materials and the phase‐pure FAPbI3, wide‐gap perovskite still suffers from huge voltage deficits. Here, the authors take advantage of the synergetic effect behind a sequential fluoride and organic ammonium salt surface passivation strategy to control non‐radiative energy losses, and obtained a 17.7% efficiency in infrared‐transparent wide‐gap perovskite solar cells (21.1% for opaque device), and achieved efficiencies of over 25% when stacked with commercial Si and CIGS products with original PCEs of 18–20% under a 4‐terminal working condition. Abstract : A successive surface treatment of alkali fluoride and organic ammonium salt for wide bandgap perovskite that synergistically passivates their surface defects is developed for highly efficient stacked tandem applications.